Transformational Leadership And Employee Performance : Systematic Literature Review - Indah Adawiyah; Sopiah Sopiah (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to analyze the effect of transformational leadership on employee performance. The method used by this study uses the Preferred Reporting Item for Systematic Review and Meta Analysis of research that has a relationship with the influence of transformational leadership and employee performance. The data collection method uses 3 accesses, namely Science Direct, Emerald and Google Scholar. The results of this study indicate that there are 6 data that have a significant positive effect and dominate, 6 data with a positive and significant effect but do not dominate, and 3 data have a significant negative effect, 8 data show the effect of transformational leadership on employee performance through mediating variables, and 1 effect of transformational leadership on employee performance data through moderating variables. Conclusion, that transformational leadership affects employee performance where the better the application of transformational leadership in the organization, the more it improves employee performance.